EVALUASI KESUBURAN TANAH DI DUSUN KEKAWII III DESA RANDOTONDA KECAMATAN ENDE KABUPATEN ENDE - Sebastianus Kuswara; Charly Mutiara (AGRICA, 2018)
Evaluation soil fertility in dusun kekawii III randotonda Village, Ende District, Ende Regency. This study aims to determine the physical properties of the soil and the level of suitability of the land in Kekawii III hamlet, Randotonda village, Ende District, Ende Regency. Research is exploratory research, by evaluating physical properties, the evaluation results are described and compared with the standard physical properties of existing soil. The results of the study show that the soil properties in Kekawii III Hamlet are the soil texture of the sandy soil, clay. In structures, the types that exist are rounded lumps, lumpy angles, granular structures. On the color of the land dominated by Dark brown, Very dark gray, Very dark grayish brown. The consistency of land, it can be seen that these lands have a consistency that is sticky, plastic, loose, soft. The pH of the soil ranges from 4.2-6.4 and the slope ranges from 5% - 12%